Work–Life Balance, Lingkungan Kerja, dan Kesehatan Mental Sebagai Prediktor Kinerja: Peran Mediasi Kepuasan Kerja pada Ruko Araya Tahap 1 Surabaya - Nova Alfina; Anita Asnawi; Andry Herawati; Galuh Ajeng Ayuningtyas (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The phenomenon of high work pressure and the instability of the psychological condition of employees in small businesses prompts the need for a comprehensive study of the factors that shape their performance. This study aims to analyze the influence of work-life balance (WLB), work environment (WE), and mental health (MH) on employee performance (WP), with job satisfaction (JS) as a mediating variable in employees working at Ruko Araya Phase 1 Surabaya. The quantitative method was used through the distribution of questionnaires to 109 respondents, which were then analyzed using Structural Equation Modelling (SEM). The results showed that WLB and MH had a significant effect on JS, while WE did not show a significant effect. JS has proven to be instrumental in improving WP and mediating the relationship between WLB and WP. On the other hand, MH affects performance directly or indirectly through JS. These findings confirm that the psychological aspect of employees has a more dominant role than structural conditions in the small business environment. The practical implications of this study emphasize the importance of policies that support work-life balance and mental health to sustainably strengthen employee satisfaction and productivity.